2022
DOI: 10.3390/biom12060800
|View full text |Cite
|
Sign up to set email alerts
|

Breaching Brain Barriers: B Cell Migration in Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is an inflammatory disease of the central nervous system (CNS) known for the manifestation of demyelinated lesions throughout the CNS, leading to neurodegeneration. To date, not all pathological mechanisms that drive disease progression are known, but the clinical benefits of anti-CD20 therapies have put B cells in the spotlight of MS research. Besides their pathological effects in the periphery in MS, B cells gain access to the CNS where they can contribute to disease pathogenesis. Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 174 publications
0
8
0
Order By: Relevance
“…B cells then infiltrate the brain via the vessels bilaterally following stroke [65], and are capable of producing pro-or anti-inflammatory cytokines, depending on subtype, to exert influence on processes including T-cell antigen-dependent inflammation and neuronal survival [98]. Another mechanism by which B cells may infiltrate the CNS is across the blood-cerebrospinal fluid barrier (BCSFB) in the choroid plexus, which occurs in a two-step process [76]. First, B cells must diapedese across capillaries into the choroid plexus stroma and then breach the transepithelial cell barrier to enter the CSF.…”
Section: Early Recruitment Of B Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…B cells then infiltrate the brain via the vessels bilaterally following stroke [65], and are capable of producing pro-or anti-inflammatory cytokines, depending on subtype, to exert influence on processes including T-cell antigen-dependent inflammation and neuronal survival [98]. Another mechanism by which B cells may infiltrate the CNS is across the blood-cerebrospinal fluid barrier (BCSFB) in the choroid plexus, which occurs in a two-step process [76]. First, B cells must diapedese across capillaries into the choroid plexus stroma and then breach the transepithelial cell barrier to enter the CSF.…”
Section: Early Recruitment Of B Cellsmentioning
confidence: 99%
“…While much attention has been given to the diapedesis of leukocytes across the blood-brain barrier, immune cells may also infiltrate the brain by migrating over the bloodmeningeal barrier (BMB) and the BCSFB in the choroid plexus [76]. Recent research has greatly advanced our understanding of how these alternative barriers in the meninges and choroid plexus are immunologically vibrant sites of not just B cell migration, but also maturation, tolerance, and dysregulation.…”
Section: B Cells In the Meningesmentioning
confidence: 99%
“…Another brain barrier is the blood–cerebrospinal fluid barrier (BCSFB), which is formed by the epithelial cells lining the choroid plexus [ 94 ]. Besides acting as the main producer of cerebrospinal fluid (CSF), this highly vascularized tissue facilitates migration of peripheral immune cells into the CSF, thereby serving as an immunological niche enabling immunosurveillance [ 81 , 95 , 96 ]. The tight junctions, adherent junctions and gap junctions between the epithelial cells are essential for the regulation of the permeability, integrity and polarity of the BCSFB [ 94 ].…”
Section: Migratory Capacity Of Cd56 Bright Nk Cellsmentioning
confidence: 99%
“…The study also found that migration of such memory B-cells was reduced in multiple sclerosis (MS) patients treated with natalizumab, suggesting an emphasis on the role of BCSFB as an important channel for activated B-cells to enter the cerebrospinal fluid ( Haas et al, 2020 ). The important role of B-cells in diseases of the central nervous system (CNS), particularly in multiple sclerosis, emphasizes the ways in which B-cells contribute to neuropathology by secreting antibodies and neurotoxic molecules as well as presenting antigens ( Rodriguez-Mogeda et al, 2022 ).…”
Section: The Role Of B-cells At the Acute Phase After Strokementioning
confidence: 99%